Iron‐rich nanoparticles formed by aeolian abrasion of desert dune sand. (23rd September 2013) - Baddock, Matthew; Boskovic, Lucija; Strong, Craig; McTainsh, Grant; Bullard, Joanna; Agranovski, Igor; Cropp, Roger
<x xml:space="preserve">Abstract</x> [1] Iron‐rich nanoparticles in aeolian mineral dust are of considerable importance to biogeochemical cycles. A major determinant of the chemical characteristics of nanoparticles is the parent sediment they are sourced from. The abrasion of dune sand has previously been shown to produce coarse dust (>1 μm) during the occurrence of aeolian saltation. In this study, Australian red dune sands were laboratory abraded and emission of particles 18–414 nm was observed throughout the experiment duration (∼1 h). The mean size of particles was 130 nm at the start of the test, but this gradually decreased to 110 nm at the end. The number concentration of particles approximately trebled over the course of the experiment with results suggesting that collisions between mobile sand grains led to the production of new nanosized particles over time. Chemical analysis revealed that these nanoparticles were highly abundant in iron, with some aluminium present. This chemical composition suggests that nanoparticles are produced from the clay coatings surrounding the parent sand grains. The study shows that abrasion from saltation occurring in Australian dune sands can release iron‐rich nanoparticles, making them available for downwind transport during blowing dust events.